2010
DOI: 10.1038/nature08835
|View full text |Cite
|
Sign up to set email alerts
|

Ancient human genome sequence of an extinct Palaeo-Eskimo

Abstract: We report here the genome sequence of an ancient human. Obtained from ∼4,000-year-old permafrost-preserved hair, the genome represents a male individual from the first known culture to settle in Greenland. Sequenced to an average depth of 20×, we recover 79% of the diploid genome, an amount close to the practical limit of current sequencing technologies. We identify 353,151 high-confidence single-nucleotide polymorphisms (SNPs), of which 6.8% have not been reported previously. We estimate raw read contaminatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
637
0
29

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 771 publications
(685 citation statements)
references
References 37 publications
19
637
0
29
Order By: Relevance
“…Deamination-based damage, as the most common modification in ancient DNA 5,6 , potentially complicates correct identification of base substitutions that result from evolutionary processes. The sequencing of a 4,000-year-old palaeo-eskimo's DNA sequence demonstrated that exclusion of postmortem, damage-based changes had little impact on the high-throughput sequencing result 5 .…”
Section: Overall Sequencing Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deamination-based damage, as the most common modification in ancient DNA 5,6 , potentially complicates correct identification of base substitutions that result from evolutionary processes. The sequencing of a 4,000-year-old palaeo-eskimo's DNA sequence demonstrated that exclusion of postmortem, damage-based changes had little impact on the high-throughput sequencing result 5 .…”
Section: Overall Sequencing Resultsmentioning
confidence: 99%
“…The sequencing of a 4,000-year-old palaeo-eskimo's DNA sequence demonstrated that exclusion of postmortem, damage-based changes had little impact on the high-throughput sequencing result 5 . However, to estimate the extent of miscoding lesions (that is, postmortem changes in DNA), we determined the transition and transversion ratios (Supplementary Table S2 and Supplementary Table S3) and found them to be largely consistent with ratios observed for other genomes recently analysed by high-throughput sequencing.…”
Section: Overall Sequencing Resultsmentioning
confidence: 99%
“…Another commonly used approach is to apply quality filters that are aimed at selectively removing errors. Every whole-genome sequence reported so far has used filtering to some extent: the most commonly used filters being those that remove sequences with a too-low coverage depth, discard variants with a low-confidence score or eliminate variants located within a cluster of variants 3,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . Surprisingly, there is little consensus with respect to which filters should be used and at which threshold they should be applied.…”
mentioning
confidence: 99%
“…G r e e n p l a n t s Metagenomes (multiple species) P r o t o z o a N o n -h u m a n v e r t e b r a t e s H u m a n s I n v e r t e b r a t e s First drafts of two composite haploid human genomes 1,2 Human Genome Project completed 3 Two Korean males including Seong-Jin Kim 9,10 , Stephen Quake 11 , another cancer genome 12 , George Church, a Yoruban female, another male 13 , and four others [14][15][16] A glioma cell line 17 , Inuk 18 , !Gubi and Archbishop Desmond Tutu 19 , James Lupski 20 , and a family of four 21 James Watson 5 , a woman with acute myeloid leukemia 6 , a Yoruba male from Nigeria 7 and the first Asian genome 8…”
Section: Iru Se S Ba Ct Er Ia An D Ar Ch Ae a Fun Gimentioning
confidence: 99%